Anterior Cervical Corpectomy and Fusion for Degenerative and Traumatic Spine Disorders, Single-Center Experience of a Case Series of 119 Patients. Issue 1 (31st July 2020) - Tatter, Charles; Persson, Oscar; Burström, Gustav; Edström, Erik; Elmi-Terander, Adrian
Abstract: BACKGROUND: Anterior cervical corpectomy and fusion (ACCF) is a treatment option for several cervical pathologies. Various graft materials such as autografts, titanium mesh cages (TMC), or poly-ether-ether-ketone (PEEK) cages are used. Additional posterior fixation (PF) to provide extra support and improve stability is sometimes performed initially, or later as supplementary treatment. OBJECTIVE: To describe our retrospective study of 119 consecutive cases of ACCF with synthetic grafts, in 3 cohorts of cervical spondylotic myelopathy (CSM), infectious and neoplastic processes, and trauma, with special focus on need for supplementary PF. METHODS: A total of 135 adult patients treated with ACCF between January 2005 and January 2018 were identified. Patients lost to follow-up were excluded, and 119 remaining patients were included for retrospective clinical and radiological assessment. RESULTS: Synthetic grafts were used in 116 (97%) cases. Only 9 (8%) ACCF cases required later supplementary PF, where 7 (78%) cases were multilevel. There was a statistically significant difference in revision rate with PF for single-level compared to multilevel ACCFs ( P  = .001). Revision rates with PF were 2%, 29%, and 7% in CSM, infectious and neoplastic processes, and trauma cohorts, respectively. CONCLUSION: The results indicate that ACCF is a safe and effective treatment for degenerative and traumatic cervical spine disorders, with low complication and revision rates. Single-level ACCF can be performed without additional PF. Multilevel ACCF (n > 2) and pathologies affecting bone quality seem to be risk factors for material subsidence and instability. In these cases, additional PF should be considered. Graphical Abstract: